Multi-factorial analysis of the removal of dichloromethane and toluene in an airlift packing bioreactor. (1st May 2020) - Xu, Peilun; Wei, Yang; Ma, Cunhao; Li, Sujing; Guo, Tianjiao; Wang, Xiangqian; Li, Wei
Abstract: Biotechnology has proven effective in removing a wide variety of VOCs. In this study, the effects of pH (from 3 to 7), operating temperature (20 − 30 °C), empty bed residence time (EBRT, 10 − 40 s) and transient inlet concentration (400 − 4000 mg m −3 ) on the removal performance of an airlift packing bioreactor (ALPR) was investigated. The removal efficiency (RE) and stability of the ALPR was evaluated and compared with the conventional airlift bioreactor (ALR). The results showed that under the influence of single factor variation, the ALPR showed significant higher RE and better stability than the ALR in removing dichloromethane (DCM) and toluene. Besides, a factorial design was used to analyses the interaction of multiple factors and their influence on the removal of DCM and toluene in the ALPR and ALR. It shows that pH value has the most significant influence, and plays a crucial role in maintaining high RE of DCM and toluene in both of the ALPR and ALR. Temperature has a great effect on the removal of toluene. EBRT has certain effect on the removal of DCM in the ALPR. The transient concentration of a single substrate has a significant negative effect on the RE of this substrate, while it does not significantly affect the removal of another substrate in the ALPR. However, the steep increase of DCM concentration has an adverse effect on the RE of high concentration toluene in the ALR. The overall RE and degradation capacity of both toluene and DCM by the ALPR are much higher than that of the conventional ALR. Highlights: The airlift packing reactor showed superior stability than the airlift reactor. Factorial design was used to study the interactions of multiple factors. pH has the most significant positive effect on the removal of DCM and toluene. The inlet concentration transient has the most significant negative effects.